Pemberdayaan Holistik Warga Gereja Berbasis Integrasi Spiritualitas, Kewirausahaan Sosial, dan Literasi Ilmiah Remaja Jemaat GPM Petra: Pengabdian - O. Amtu; Wilhelmus Labobar; Cynthia. L. Sapulette; Hendra Helwaun; Claudia. M. Pattiruhu; Flora Maunary; Sanny. T. Sapulete; Meike. E. Toisuta; Franklin. S. Dahaklory; Franklin Untailawan; Yamres Pakniany; Asweres. A. F. Termas (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
As part of the implementation of the GPM Petra Congregational Program 2025, particularly in the development of SMTPI children and catechism students, a one-day community service (PkM) activity was conducted through a participatory approach. This activity aimed to strengthen the spirituality and personal capacity of teenagers, considering that only 35% of youth aged 13–20 are actively involved in spiritual activities. The training materials included creative spiritual development, Bible-based social entrepreneurship, popular scientific writing skills, and ethical language and social media literacy. As a result, the youth developed a deeper understanding of their identity as members of the Church, were able to reflect Christian values in their behavior, fostered an entrepreneurial spirit through a flower booklet business and digital marketing, and demonstrated critical thinking and problem-solving skills both within the Church and in their social environment.